2014
DOI: 10.1007/s00062-014-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Histological Clot Composition in Embolic Stroke

Abstract: Our results suggest that thrombi with a high WBC fraction are related to more organized thrombi of cardioembolic origin associated with less favorable recanalization and clinical outcome in acute ischemic anterior circulation stroke. WBC-mediated immunological and coagulatory processes may play a key role in thrombus formation and pathogenesis of stroke warranting further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
209
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(227 citation statements)
references
References 30 publications
11
209
4
3
Order By: Relevance
“…This supports recent studies by Boeckh-Behrens et al, 8,10 Niesten et al, 13 and Simons et al, 7 that report about an association of high fibrin and low RBC proportion in cardioembolic thrombi and which are contrary to the concept of red and erythrocyte-rich cardioembolic thrombi (Figure 1). The contradictory findings of Kim et al 14 may be related to differences in methods and study population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This supports recent studies by Boeckh-Behrens et al, 8,10 Niesten et al, 13 and Simons et al, 7 that report about an association of high fibrin and low RBC proportion in cardioembolic thrombi and which are contrary to the concept of red and erythrocyte-rich cardioembolic thrombi (Figure 1). The contradictory findings of Kim et al 14 may be related to differences in methods and study population.…”
Section: Discussionsupporting
confidence: 90%
“…[3][4][5][6][7][8][9] Moreover, first results about the differentiation of cardioembolic versus noncardioembolic stroke suggest that cryptogenic stroke is mostly of cardiac origin. 8,10 However, evidence is limited, especially for immunohistochemical parameters. 11 Our study, therefore, aimed to evaluate further the theory of histological determination of thrombus origin and additionally included immunohistochemical parameters that may help to specify the thrombus origin.…”
Section: Background and Purposementioning
confidence: 99%
“…To date, very few studies investigating a possible relationship between the histology of retrieved clots and stroke mechanisms have been reported. [8][9][10] Moreover, the results of previous studies have been inconsistent and confusing. Liebeskind et al 10 performed histopathologic analysis of retrieved clots in 50 patients with acute ischemic stroke who had undergone endovascular thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that histologic examination of retrieved clots can offer new insights into the pathogenesis of acute stroke due to intracranial large-vessel occlusion. [6][7][8][9] However, it is currently unclear whether clot-composition analysis is helpful to predict a stroke mechanism in acute large-vessel occlusion. Only a few studies have been conducted on this topic, and prior studies have yielded only vague and contradictory results.…”
mentioning
confidence: 99%
See 1 more Smart Citation